A Broad Range Triboelectric Stiffness Sensor for Variable Inclusions Recognition - Ziyi Zhao; Zhentan Quan; Huaze Tang; Qinghao Xu; Hongfa Zhao; Zihan Wang; Ziwu Song; Shoujie Li; Ishara Dharmasena; Changsheng Wu; Wenbo Ding (Nano-Micro Letters)
Highlights We propose a broad range triboelectric sensor system employing elastic sponge and shielding layers, which can realize fast stiffness recognition within 1.0 s at a low cost. A novel algorithm is proposed for rapid stiffness identification by extracting signal characteristics, effectively reducing demand of computing resources. The proposed sensor system can identify the multi-layer stiffness structure of objects, enabling effective recognition of variable inclusions in soft objects with an accuracy of 99.7%.